ANALISIS FAKTOR – FAKTOR PRODUKSI USAHATANI PADI GOGO DI KABUPATEN KEBUMEN - Ade Ruskandar; Elis Septianingrum; Widyantoro Widyantoro (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2019)
The efforts to increase rice production is still focused on irrigated paddy field, especially by intesification. On the other hand, there are other land resources, such as dry land that can be used for rice extensification by cultivating upland rice. Dry land area in Kebumen regency reaches 88.364 ha. This number gives a significant meaning to the total rice production in Kebumen. The objective of the study was to investigate the variability of the farming bussiness and the factors influencing upland rice production in Mirit district, Kebumen regency. The variability of farming bussiness in the regency could be seen from several thing. Upland rice varieties (Inpago 8, Situ Bagendit, dan Situ Patenggang) used in one planting cropping pattern per year. Planting was carried out by tugal (3-4 seeds/hole). Seeds used were non-labeled and produced from government assistance of farmers’ group. Manpower was needed at land cultivation, planting, harvesting, threshing, and drying of the paddy. The workforce mostly were men and came from farmer’s family. The women were only utilitized on planting activity. F test showed that the number of workers, seeds, urea, SP, and KCl, NPK, compost fertilizer, and seeds’ type were simultaneously affecting production result and t-test indicated that the number of SP, NPK, and manure fertilizer partially affecting the production of upland rice.